Deep Learning Approaches for Protein Structure Prediction - Chandni, Khatri; Mrudang Pandya, Prof.; Sunil Jardosh, Dr. (International Journal of Engineering and Technology, 2018)
In recent years, Machine Learning techniques that are based on Deep Learning networks that show a great promise in research          communities.Successful methods for deep learning involve Artificial Neural Networks and Machine Learning. Deep Learning solves severa  problems in bioinformatics. Protein Structure Prediction is one of the most important fields that can be solving using Deep Learning  approaches.These protein are categorized on basis of occurrence of amino acid patterns occur to extract the feature. In these paper aimed to review work based on protein structure prediction solve using Deep Learning Networks. Objective is to review motivate and facilitatethese deep learn the network for predicting protein sequences using Deep Learning.
Keywords: Bioinformatics; Protein Contact Mapping; Protein-Protein Interactions; Protein Structure Prediction; Protein Docking; Protein Folding; DeepLearning